EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF PADA PELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL (IPAS) DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS V DI SD S TIGA HATI KEPENUHAN HULU (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Interactive learning media based on animated videos has an attractive visual appeal that can stimulate students to analyze, think, be motivated, and enhance students' interest in learning. The aim of this research is to determine the effectiveness and impact of using interactive learning media in social studies (IPS) to increase students' interest in learning. The subjects of this research consisted of 29 fifth-grade students at SD S Tiga Hati Kepenuhan Hulu. This study utilized classroom action research (CAR) methods obtained through observation, interviews, questionnaires, and documentation. The results showed an increase in students' interest in learning in each cycle, with the highest success rate in cycle II at 94% (very good) and the lowest in the pre-cycle at 39.9% (poor). This research can be concluded as successful and effective in enhancing students' interest in learning.